MONEY POLITICS IN ELECTIONS: A STUDY OF REGULATION AND PRATICE IN INDONESIA - Saepul Ahyar, Usep (Universitas Serang Raya, 2025)
Abstract Problem: The 2024 simultaneous elections; presidential, legislative and regional elections, leave systemic problems, including; the rampant use of money politics which disrupts the integrity of the election and the enforcement of democracy. Money politics is the practice of buying and selling votes by giving money or services to increase the number of votes in the election. Objective: to answer the complexity of the phenomenon of money politics caused by loopholes in election regulations by empirically confirming money politics in practice. Methodology: This study uses a type of normative-empirical legal research, namely analyzing the Election Law with empirical experience. Research Findings/Results: It can be seen that the Election Law and various regulations so far still provide quite wide loopholes for the practice of money politics, including: limited legal subjects, very limited objects of regulation at election stages, different criminal threats in election regulations, especially elections and elections (regional elections) which are quite confusing. In addition, there is a political recruitment system carried out by political parties that is quite vulnerable and crucial in money politics, in addition there are several election systems that are vulnerable and provide loopholes for money politics, including: the open proportional election system and the presidential threshold. Keywords: Democratic Election; Election Law; Money Politics, and Election System Reform.